Práticas de governança corporativa das operadoras de Planos de Saúde Suplementar do Brasil - Silva, Francisco Juanito Costa da (2019)
The supplementary health market exceeds 47 million beneficiaries, which represents 23% of the Brazilian population. These data show the magnitude of the sector, which in December 2018 had 968 active supplementary health operators (operators with beneficiaries), operating in all regions of the country, with annual revenues of R $ 139 million (ANS, 2019). Health Plan Operators (OPS) are legal entities constituted in the form of a business, association, foundation, cooperative or self-management entities, mandatorily registered with the regulatory agency of the supplementary health market (ANS, 2000). These OSPs must maintain high standards of controls to provide credibility to those involved, therefore using KM practices, which are a set of procedures that seek a competitive advantage to offer investors and potential creditors. Thus, they contribute to guarantee the rights of shareholders, protect minority shareholders and avoid possible abuses by managers (MOKEN et al., 2015). This research aims to analyze the degree of adherence to the corporate governance practices of the supplementary health insurance operators in Brazil. For this purpose, a descriptive and documentary research was used, collecting material on the electronic portals of the health insurance companies studied. It was characterized by the corporate governance practices used by the supplementary healthcare operators and were identified and classified according to their modalities and level of adherence. Four levels of adherence were adopted, but only two were verified: low, adopted in group and philanthropic modalities; and moderate, for medical cooperatives, self-management and insurance. It was also found that the size and scope are positively related to the OSP's corporate governance practices. Thus, it was concluded that the corporate governance practices adopted by supplementary health operators are predominantly restricted to those legally imposed, referring to the standard dictated by the market and the regulatory agency.